Brand mergers: an analysis of consumer brand identity preferences - César Machado, Joana (2011)
Purpose- The purpose of this study is to investigate reactions to the various name and logo redeployment alternatives available in the context of a merger. Design/methodology/approach - This study develops a typology of the alternative visual identity structures that may be assumed in the context of a brand merger by drawing on literature review and secondary data, as well as an exploratory study (n = 467) analysing consumers’ preferences regarding the alternative brand identity strategies. Findings – Results suggest that there is a clear preference for figurative brand logos. Furthermore, we found evidence that the brand logo may play a role as important as the name in a merger, ensuring consumers that there will be a connection with the brand’s past. Another interesting finding was that the choice of the logo reflects consumers’ aesthetic responses, whereas the choice of the name reflects consumers’ evaluation of the brand’s offer or off the brand’s presence in the market. Originality/value – The paper uses an innovative research design which gives respondents freedom to choose their preferred solution, hence the richness of results is much greater. These results should guide managers in the evaluation and choice of the post-merger branding strategy.